Does the cranial suspensory ligament have a role in cryptorchidism? - Kassim, N.M.; Russell, D.A.; Payne, A.P. (Karger Publishers, 2010)
The cranial suspensory ligament (CSL) is a fibromuscular structure anchoring the embryonic gonad to the posterior abdominal wall in male and female mammals. Its persistence in females is believed to be responsible for retaining the ovaries within the abdomen, while its regression in males permits testis descent. Embryonic loss of the CSL in males is believed to be an androgen-dependent event, and failure of this process has been proposed as a cause of cryptorchidism. The present study demonstrates that the nuclei of mesenchymal cells in the caudal part of the CSL are immunoreactively positive for androgen receptor. We examined the effects of exposure of the non-steroidal antiandrogen flutamide during the period from gestational day 10 to birth on the development of the CSL and on testis descent. Exposure of male Albino Swiss rats to the antiandrogen flutamide during this period resulted in feminization of the external genitalia and the suppression of growth of the testes and male reproductive tracts. In adulthood, testes were found to be located in diverse positions including normal scrotal (50%), intra-abdominal (10%) and ectopic suprainguinal (40%). The CSL of the testis persisted into adulthood in all flutamidetreated males, regardless of testis location. In all cases, the ligament consisted of bundles of smooth muscle fibres in the retroperitoneal fat of the posterior abdominal wall. These findings suggest that androgen blockade during embryonic development interferes with testicular descent, but that maldescent cannot be correlated with either the persistence of the CSL of the testis or its structure. Copyright (C) 2009 S. Karger AG, Basel